One day as a lion [videorecording (DVD)] - Caan, Scott, 1976-; Caan, Scott, 1976-; Grillo, Frank, 1963-; Rendón, Marianne; Manning, Taryn; Slaine, 1977-; Madsen, Virginia, 1961-; Simmons, J. K. (Lionsgate, 2023)
Jackie Powers will stop at nothing to prevent his son from following him into a life of crime. With his mob employer in pursuit, a chance encounter at a roadside diner charts a new path.